2022
DOI: 10.1101/2022.11.24.22282708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CURATE.AI – AI-derived personalized tacrolimus dosing for pediatric liver transplant: A retrospective study

Abstract: Tacrolimus is the cornerstone of immunosuppressive therapy after pediatric liver transplantation. However, reliance on the physician's experience for dose titration, coupled with tacrolimus's narrow therapeutic window and inter and intra-patient variability, often results in frequent under or over-dosing with detrimental patient outcomes. Existing predictive dose personalization models are not readily feasible for clinical implementation, as they require multiple measurements each day while the standard freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Accordingly, collaborative functioning together with awareness, evidence, patient safety and data were key aspects that de ned CURATE.AI adoption by doctors as gauged in a formal, behavioral study. 19 Usercentered design may contribute to realizing the potential of CURATE.AI and other CDSS and their adoption at-scale. A systematic review of higher level CDSS in oncology concluded that CDSS failed to improve clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, collaborative functioning together with awareness, evidence, patient safety and data were key aspects that de ned CURATE.AI adoption by doctors as gauged in a formal, behavioral study. 19 Usercentered design may contribute to realizing the potential of CURATE.AI and other CDSS and their adoption at-scale. A systematic review of higher level CDSS in oncology concluded that CDSS failed to improve clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The small-scale experiments mentioned in earlier sections have paved the way for CURATE.AI-based retrospective studies over the years. [ 79 80 81 ] The retrospective studies serve to assess the feasibility of prospective trials for CURATE.AI, help formulate hypotheses, identify potential risk factors and assist in trial designs. Some of these studies have progressed to clinical trials for further validation [ Table 1 ].…”
Section: Curateai and N-of-1 Medicine: Use Casesmentioning
confidence: 99%
“…CURATE.AI has been clinically assessed across multiple indications, ranging from oncology to immunosuppression. These have included prospective, interventional studies, as well as retrospective analysis studies [8][9][10][11][12][13][14][15]. It has also been explored in the domain of personalized cognitive training in healthy individuals [16].…”
Section: Introductionmentioning
confidence: 99%